Current Severe Depressive Episode in Bipolar II Disorder with Anxious Distress and Post-traumatic Stress-Disorder with Derealization: a Case Report - Jaya, Muhammad Alim; Haris, Andi Jihan Nashila; Syahrir, Andi Karlina (Jurnal Psikiatri Surabaya, 2024)
Introduction: Bipolar II disorder experiences more frequent episodes of depression and is sometimes comorbid with post-traumatic stress disorder (PTSD). However, there is no clear method to distinguish between depression induced by bipolar disorder and PTSD. Through this case, we aim to examine the features of the patient’s bipolar disorder and PTSD from the depressive episodes. Case: A 23-year-old Indonesian woman came with the chief complaint of unexplainable discomfort that had been experienced almost daily for the past two weeks. The patient also complained that she was often lonely. Patients did not get adequate parenting from her parents, so patients have unfavorable relationships with her family. In addition, patients previously experienced sexual harassment that caused severe trauma. She was diagnosed with a current severe depressive episode in bipolar II disorder with anxious distress and PTSD. Discussion: Bipolar disorder is frequently comorbid with PTSD. She was given Sertraline 25 mg once daily, Aripiprazole 5 mg twice a day, Clobazam 5 mg once a day at night, Folic acid 400 mcg once a day, and psychotherapy. After four weeks of treatment, there was an improvement in symptoms by a decrease in the HDRS and the HARS scores. Conclusion: In the case presented, bipolar patients have major complaints related to somatic symptoms accompanied by a history of experiencing severe traumatic events. Thus, bipolar patients do not always come with the chief complaint of mood swings. Furthermore, these complaints improved with the combination of anti-psychotic, anti-depressant, anti-anxiety, and psychotherapy.